Evaluation of the completeness and timeliness of the infant pertussis surveillance system in the Czech Republic in 2015, 2017 and 2019 - Liptakova, Monika (Zdravstveno varstvo, 2023)
Introduction: The completeness and timeliness of the pertussis questionnaire-based enhanced surveillance system (ESS) among infants and reported pertussis data within the electronic nationwide notification system (NNS) in the years 2015, 2017 and 2019 were evaluated in a pilot study. Methods: The completeness of the variables for demographic characteristics, date of symptom onset, hospitalisation and vaccination status were assessed in both systems. Timeliness of reporting in the NNS was analysed as the interval between symptom onset and a) the date of first specimen collection (diagnostic delay), and b) the date of the Regional Public Health Authority receiving notification (notification delay). Results: A total of 121 confirmed pertussis cases were reported to the NNS in the study years, while in the ESS a total of 104 confirmed cases were reported in infants. In both systems most cases were in the age group of one completed month of life (20% versus 23%) and males (55% versus 55%). The majority of cases were hospitalised (81% versus 85%) and unvaccinated (77% versus 78%). Within the NNS, the first dose of vaccine was reported in 13 cases, the second dose in 11, and third dose in three cases. Within the NNS, 100% completeness of following variables was found: symptom onset, week and region of reporting, age, gender and place of isolation. Median diagnostic delay was nine days. Median notification delay was 18 days. Conclusions: Data completeness was high in the NNS, except for lack of vaccination data in those eligible by age. Efforts to improve the completeness of laboratory-related variables and timeliness are essential. Based on the study results, the project of improving the ESS for infants will continue with regular evaluation.
Keywords: completeness; dojenčki; infants; oslovski kašelj; pertusis; pertussis; pravočasnost; spremljanje; surveillance; timeliness; whooping cough